Refleksi Orientalisme, Oksidentalisme, dan Oksidentalis: Kajian terhadap Hubungan Timur dan Barat dalam Studi Islam - Indria Hartika Rukmana; Ihsan Kamaludin (JURNAL KEMUHAMMADIYAHAN DAN INTEGRASI ILMU, 2023)
Occidentalism is a concept that emerged as a response to Orientalism in the West. Orientalism is a viewpoint, thought, and study conducted by the West towards the Eastern world, often creating an attitude of Western superiority towards the East. As a counter-discourse to Orientalism, Occidentalism emerged as an attempt from Eastern societies to respond to Orientalism and reassess the West as an object of study. Several Muslim thinkers, such as Hasan Hanafi, Mukti Ali, Burhanuddin Daya, Alef Theria Wasim, Muzaeri, Amin Abdullah, and Al Makin, have contributed to the concept of Occidentalism. They propose research and critical study of the West, as well as attempts to understand the role of the West in Eastern civilization. Hasan Hanafi introduced occidentalism as a tool to confront the West's profound influence on Eastern civilization. Other thinkers, such as Mukti Ali, Burhanuddin Daya, and Alef Theria Wasim, discussed the importance of studying Occidentalism as a response to Orientalism. Muzaeri highlighted conceptual and ideological issues in Occidentalism, while Amin Abdullah emphasized the integration between science and religion in Islamic academic circles. Occidentalism is essential in promoting dialogue and better understanding between the West and the East in the current era of globalization. The concept still requires further development and in-depth study to understand its implications in recent developments.